Massive Epistaxis Related to Petrous Carotid Artery Pseudoaneurysm After Radiation Therapy: Emergency Treatment with Covered Stent in Two Cases - Auyeung, Kai Ming; Lui, Wai Man; Chow, Lawrence C.K.; Chan, Fu Luk (American Journal of Neuroradiology, 2003)
Summary: Two patients had acute left carotid rupture from radiation therapy-induced pseudoaneurysms, resulting in hemodynamic collapse. Because the patients were semicomatose and in shock, an immediate salvage procedure was needed. Location of the pseudoaneurysm at the skull base made surgical treatment less possible. Endovascular therapy was the treatment of choice. Preserving patency of the carotid artery was a desirable option. The successful use of a covered stent in the emergency treatment of massive epistaxis due to active bleeding from pseudoaneurysm in the petrous internal carotid artery (ICA) is described.